Molecular Characterization and Chemotactic Function of CXCL8 in Northeast Chinese Lamprey (Lethenteron morii) - Zhu, Xinyun; Zhang, Zhe; Ren, Jianfeng; Jia, Liang; Ding, Shaoqing; Pu, Jiafei; Ma, Wenyuan; Tao, Yan; Zu, Yao; Li, Weiming; Zhang, Qinghua (Frontiers in Immunology, 2020)
Chemokine-induced chemotaxis of leukocytes is an important part of the innate immunity, and has been shown to mediate inflammation in all groups of jawed vertebrates. For jawless vertebrates, hagfish leukocytes are known to show chemotaxis toward mammalian complement anaphylotoxin and Gram negative bacteria lipopolysaccharide (LPS). However, whether chemokines mediate chemotaxis of leukocytes in jawless vertebrates have not been conclusively examined. Here we show C-X-C motif chemokine ligand 8 (CXCL8, also namely Interleukin 8) of the Northeast Chinese lamprey (Lethenteron morii) (designated as LmCXCL8) induces chemotaxis in its neutrophils. We identified LmCXCL8 and found it possesses the characteristic N-terminal cysteine residues and GGR (Gly-Gly-Arg) motif. The Lmcxcl8 gene was found to be expressed in all examined tissues, and its expression was inducible in the lamprey challenged by an infectious bacterium, Pseudomonas aeruginosa. A recombinant LmCXCL8 protein elicited concentration dependent chemotaxis in peripheral blood leucocytes (PBLs) isolated from the Northeast Chinese lamprey. Based on these results, we conclude that LmCXCL8 is a constitutive and inducible acute-phase cytokine that mediates immune defense, and trace the chemotactic function of chemokine to basal vertebrates.